GPS Interferometric Reflectometry Reveals Cyclic Elevation Changes in Thaw and Freezing Seasons in a Permafrost Area (Barrow, Alaska). Issue 11 (12th June 2018) - Hu, Yufeng; Liu, Lin; Larson, Kristine M.; Schaefer, Kevin M.; Zhang, Jiahua; Yao, Yibin
Abstract: Ground surface over permafrost area undergoes seasonal subsidence and uplift caused by the annual thawing and freezing of the active layer. Applying the Global Positioning System (GPS) interferometric reflectometry technique to the signal‐to‐noise ratio data collected by a continuously operating GPS station in a permafrost area in Barrow, we retrieve the daily surface elevation changes on snow‐free days over a decade (2007–2016). Among these years, 2016 had the longest snow‐free season, offering the longest and most complete records of elevation changes. Use this year as an example, we show that the ground subsided in thaw season and then uplifted from September to early November (freezing season) with an amplitude of 5.1 ± 0.2 cm. We also develop a composite model that includes both thaw and freeze indices to characterize the cyclic movements. Our composite model effectively explains the observed cyclic elevation changes and could be used in other permafrost studies. Plain Language Summary: The ground surface over permafrost area subsides and uplifts annually associated with the thawing and freezing processes. We obtain continuous records of elevation changes during snow‐free days using reflected Global Positioning System (GPS) signals. Our new measurements reveal the cyclic pattern of subsidence and uplift, which is successfully quantified by a new and simple model that accounts for both thawing and freezing. These observations are important for a quantitative understanding of the progressive movements of frozen ground and for assessing the impact of elevation changes on natural environments and infrastructure over permafrost areas. Key Points: GPS‐IR successfully retrieves ground uplifts during snow‐free days in freezing season in a continuous permafrost area GPS‐IR can provide daily records that show a cyclic pattern of thaw subsidence and freezing uplift A new composite model incorporating thaw and freeze indices can quantitatively explain the retrieved cyclic elevation changes